The prevalence of obesity and the knowledge, attitude and practice of healthy lifestyle among the adult population in Kampung Banyuk, Kampung Kerto and Kampung Langup - Wong, Syn Hwan; Wong, Vivian Chee Yien; Sofina Azurin, binti Soffian; Siti Syuhada, binti Rosman; Nur Hazwani, binti Abdul Rahman Sebli; Nur Edayah, binti Ibrahim; Nor Atikah, binti Mohamad; Noor Syafatin Azmin, binti Abdul Safar; Muhd Zarif, b Mohd Amin; Jong, Margeret Shu Y; Lee, Mei Funn; Hon, Shu Ann; et al. (Universiti Malaysia Sarawak (UNIMAS), 2013)
Background Obesity has become a great public health concern and prevent!ive measures need to be done.